Alternative in Providing Proof of Negative Exponent for Junior High School Students - Karim, Gina Silvia; Fatmawati, Naini; Wijayanti, Dyana (Universitas PGRI Madiun, 2020)
This study aims to make a contribution related to opinions and perceptions about negative exponents among junior high school students. In this study, negative exponents are considered as difficult things that require various efforts to instill good knowledge concepts in students. One of them is through evidence in learning mathematics. Evidence is considered capable of instilling students' knowledge concepts in negative exponent material. The research method used is descriptive qualitative research. Descriptive literature research studies through literature reviews, journals, and books relating to negative exponents. The results of this study are alternatives to completing formal and informal evidence related to negative exponents in junior high school students. Through some alternative evidence in introducing negative exponents is expected to make students better understand the form of negative exponents well. So that at the level above students can easily solve problems related to negative exponents without getting errors in the operation of advanced exponents.